1982
DOI: 10.1161/01.cir.66.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Coronary collateral function during exercise.

Abstract: SUMMARY A totally occluded coronary vessel subtending a noninfarcted, entirely collateral-dependent myocardial region (NIECDMR) provides an opportunity to assess collateral perfusion during exercise stress. Collateral function was determined by analysis of exercise thallium-201 myocardial perfusion images from 31 patients who had at least one NIECDMR (total 41 NIECDMRs) documented during catheterization. Twenty-two of 41 NIECDMRs manifested exercise-induced perfusion defects and 19 were normally perfused. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Berger et al (1980) and Eng et al (1982) suggest that whether collaterals arejeopardized or not may not be a major determinant affecting stress-induced ischemia, and our results are in agreement with the reports. However, Rigo et al (1979) reported that nonjeopardized coronary collateral prevented stressinduced ischemia and the jeopardized one did not, since exercise-induced perfusion defect was not demonstrated when collaterals were nonjeopardized.…”
Section: Lesion On the Donor Artery Of Collateralssupporting
confidence: 94%
“…Berger et al (1980) and Eng et al (1982) suggest that whether collaterals arejeopardized or not may not be a major determinant affecting stress-induced ischemia, and our results are in agreement with the reports. However, Rigo et al (1979) reported that nonjeopardized coronary collateral prevented stressinduced ischemia and the jeopardized one did not, since exercise-induced perfusion defect was not demonstrated when collaterals were nonjeopardized.…”
Section: Lesion On the Donor Artery Of Collateralssupporting
confidence: 94%
“…While modern myocardial perfusion imaging using positron emission tomography is able to measure actual perfusion, the only available studies investigating collateral function in response to exercise have employed thallium-201 perfusion imaging providing only a dichotomous measure of absent or present perfusion defects [22-24]. …”
Section: Fluid Shear Stress and Vasomotor Functionmentioning
confidence: 99%
“…Regarding the oxygen supply obtained by blood flow, the effort to limit the size of ischemia or infarct caused by coronary stenosis or occlusion was undertaken by coronary collateral [19,20] and microcirculation [21,22] in which a functional end arteries system exist as an end-capillary loop, particularly in the apical area within the ischemic territory [11]. Our results may illustrate the significance of the peripheral circulation for the recovery from ischemia in the apical side.…”
Section: Discussionmentioning
confidence: 78%